2021
DOI: 10.1093/imrn/rnab078
|View full text |Cite
|
Sign up to set email alerts
|

Borel and Volume Classes for Dense Representations of Discrete Groups

Abstract: We show that the bounded Borel class of any dense representation $\rho : G\to{\operatorname{PSL}}_n{\mathbb{C}}$ is non-zero in degree three bounded cohomology and has maximal semi-norm, for any discrete group $G$. When $n=2$, the Borel class is equal to the three-dimensional hyperbolic volume class. Using tools from the theory of Kleinian groups, we show that the volume class of a dense representation $\rho : G\to{\operatorname{PSL}}_2{\mathbb{C}}$ is uniformly separated in semi-norm from any other representa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In a more general setting, Francaviglia and Klaff [FK06] proved some similar rigidity results for their definition of volume of a representation Γ → PO(m, 1), this time assuming m ≥ n ≥ 3 (the rigidity of volume actually holds also at infinity, as proved by Francaviglia and the second author [FS18] for the real hyperbolic lattices: Moreover, the second author also showed that the rigidity holds for complex and quaternionic lattices [Sav18]). The interest in the study of volume of representations has recently grown, leading to the development of a rich literature [Poz15,KK16,Tho18,Fara,Farb].…”
mentioning
confidence: 99%
“…In a more general setting, Francaviglia and Klaff [FK06] proved some similar rigidity results for their definition of volume of a representation Γ → PO(m, 1), this time assuming m ≥ n ≥ 3 (the rigidity of volume actually holds also at infinity, as proved by Francaviglia and the second author [FS18] for the real hyperbolic lattices: Moreover, the second author also showed that the rigidity holds for complex and quaternionic lattices [Sav18]). The interest in the study of volume of representations has recently grown, leading to the development of a rich literature [Poz15,KK16,Tho18,Fara,Farb].…”
mentioning
confidence: 99%